2017
DOI: 10.1016/j.anaerobe.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of continuous biogas reactors operating under wet fermentation conditions to dry conditions with corn stover as substrate

Abstract: Corn stover (CS) is the agricultural by-product of maize cultivation. Due to its high abundance and high energy content it is a promising substrate for the bioenergy sector. However, it is currently neglected in industrial scale biogas plants, because of its slow decomposition and hydrophobic character. To assess the maximum biomethane potential of CS, long-term batch fermentations were carried out with various substrate concentrations and particle sizes for 72 days. In separate experiments we adapted the biog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Shortly, 35 g soil was weighed into a plastic cylinder (the bottom of which was secured with cotton fabric and a rubber band), saturated for 48 h and then placed onto damp sand to drain for 48 h. Soil organic matter was indicated by the weight loss on ignition at 550 • C for 4 h, while carbonate content in soil was measured by combustion at 950 • C for 2 h [48]. Total C and total N in soils were analyzed using a Vario MAX CN Analyzer equipment (Elementar Group, Hanau, Germany) with the operating parameters described in Kakuk et al [49]. For available P determination, the optimized colorimetric method of Franson [50] was used.…”
Section: Soil Sampling and Physicochemical Characterizationmentioning
confidence: 99%
“…Shortly, 35 g soil was weighed into a plastic cylinder (the bottom of which was secured with cotton fabric and a rubber band), saturated for 48 h and then placed onto damp sand to drain for 48 h. Soil organic matter was indicated by the weight loss on ignition at 550 • C for 4 h, while carbonate content in soil was measured by combustion at 950 • C for 2 h [48]. Total C and total N in soils were analyzed using a Vario MAX CN Analyzer equipment (Elementar Group, Hanau, Germany) with the operating parameters described in Kakuk et al [49]. For available P determination, the optimized colorimetric method of Franson [50] was used.…”
Section: Soil Sampling and Physicochemical Characterizationmentioning
confidence: 99%
“…With TSes of 15% as the limit, AD can be divided into dry AD and wet AD [66]. In general, wet AD produces more biogas than dry AD does [67][68][69][70]. In the process of AD, the TSes of the fermentation material also change with degradation [71].…”
Section: Four Single-factor Experimental Conditions: Temperature Musmentioning
confidence: 99%
“…Straw is characterized by its low bulk density, high-water holding capacity, and poor fluidity, resulting in poor heat and mass transfer, which results in detrimental non-homogeneity of the mixture that degrades digestion performance [29,38]. Mixing is deemed as very important for achieving a good distribution of the substrates, microorganisms, and enzymes in the digester, in order to optimize anaerobic digestion [39]. Ivoachu et al confirmed that recycling percolate in dry anaerobic digestion is a viable method for digesting straw more rapidly and effectively, due to the higher nutrient and microbial concentration in the recycled percolate [38].…”
Section: Mass Transfermentioning
confidence: 99%